Phytosome complex of curcumin as complementary therapy of advanced pancreatic cancer improves safety and efficacy of gemcitabine: Results of a prospective phase II trial. (June 2018) - Pastorelli, Davide; Fabricio, Aline S.C.; Giovanis, Petros; D'Ippolito, Simona; Fiduccia, Pasquale; Soldà, Caterina; Buda, Andrea; Sperti, Cosimo; Bardini, Romeo; Da Dalt, Gianfranco; Rainato, Giulia; Gion, Massimo; et al.
Graphical abstract: Abstract: A large body of biomedical evidence indicates that activation of Nrf2 by curcumin increases the nucleophilic tone and damps inflammation cumulatively supporting the malignant phenotype. Conversely, genetic analyses suggest a possible oncogenic nature of constitutive Nrf2 activation since an increased nucleophilic tone is alleged increasing chemoresistance of cancer cells. Aiming to contribute to solve this paradox, this study addressed the issue of safety and efficacy of curcumin as complementary therapy of gemcitabine on pancreatic cancer. This was a single centre, single arm prospective phase II trial. Patients received gemcitabine and Meriva ®, a patented preparation of curcumin complexed with phospholipids. Primary endpoint was response rate, secondary endpoints were progression free survival, overall survival, tolerability and quality of life. Analysis of inflammatory biomarkers was also carried out. Fifty-two consecutive patients were enrolled. Forty-four (13 locally advanced and 31 metastatic) were suitable for primary endpoint evaluation. Median age was 66 years (range 42–87); 42 patients had Eastern Cooperative Oncology Group performance status 0–1. The median number of treatment cycle was 4.5 (range 2–14). We observed 27.3% of response rate and 34.1% of cases with stable disease, totalizing a disease control rate of 61.4%. The median progression free survival and overall survival were 8.4 and 10.2 months, respectively. Higher IL-6 and sCD40L levels before treatment were associated to a worse overall survival (p < 0.01). Increases in sCD40L levels after 1 cycle of chemotherapy were associated with a reduced response to the therapy. Grade 3/4 toxicity was observed (neutropenia, 38.6%; anemia, 6.8%). There were no significant changes in quality of life during therapy. In conclusion, the complementary therapy to gemcitabine with phytosome complex of curcumin is not only safe but also efficiently translate in a good response rate in first line therapy of advanced pancreatic cancer.